Hepatic interferon‐gamma‐induced protein‐10 expression is more strongly associated with liver fibrosis than interleukin‐28B single nucleotide polymorphisms in hepatocellular carcinoma resected patients with chronic hepatitis C. Issue 11 (7th February 2013) - Konishi, Hideyuki; Shirabe, Ken; Yoshiya, Shohei; Ikeda, Tetsuo; Ikegami, Toru; Yoshizumi, Tomoharu; Ikawa‐Yoshida, Ayae; Motomura, Takashi; Fukuhara, Takasuke; Maehara, Yoshihiko
Abstract : Aim: Single nucleotide polymorphisms (SNP) around IL‐28B and interferon (IFN)‐stimulated gene (ISG) expression are predictors of response to standard therapy involving IFN for chronic hepatitis C virus (HCV) infection. We analyzed the association between these predictors to improve the prediction of the response to IFN therapy after liver resection for hepatocellular carcinoma (HCC). Methods: Data were collected from 74 patients with HCV‐induced HCC. The IL‐28B genotype and hepatic ISG mRNA levels were analyzed to clarify their association, focusing on the progression of liver fibrosis. Results: Fifty patients were identified as having major alleles ( rs8099917  TT) and the remaining 24 patients had minor alleles ( rs8099917  TG or GG). Hepatic ISG15 expression was lower in the IL‐28B major group than that in the IL‐28B minor group ( P  < 0.005). IP‐10 expression was similar between the IL‐28B major and minor groups ( P  = 0.44). IP‐10 expression was elevated with advancing stages of liver fibrosis in HCV infected patients ( P  = 0.005). In patients with mild or no fibrosis, the IL‐28B major group had lower IP‐10 expression than the IL‐28B minor group ( P  = 0.02). However, in patients with advanced fibrosis, IP‐10 expression was not different between the IL‐28B major and minor groups ( P  = 0.66). Conclusion: Hepatic ISG15 expression is associated with IL‐28B polymorphisms, while IP‐10 is strongly affected by liver fibrosis.